Host-guest complexes of two imine based isomeric 2-Lehn-type cryptands: prediction of ion selectivity by quantum chemical calculations XIX* - Adel, Alan; Puchta, Ralph; Ćoćić, Dušan; Kolenović Serezlić, Majda; Soldatović, Tanja; van Eldik, Rudi (Journal of Coordination Chemistry, 2025)
In this study the cryptands [2=N.2=N.2=N] and [2N=.2N=.2N=] were investigated using quantum chemistry methods (B3LYP/LANL2DZp). The evaluation of model reaction energy values clearly showed that in the [2=N.2=N.2=N] system, Na+ and K+ ions are best suitable for the cryptand, with a slight preference for K+. The Sr2+ is the best fitting alkaline earth ion, followed by the Ca2+ ion. [2N=.2N=.2N=] clearly prefers the smaller ions. The sodium cation is undoubtedly the favorite, with the potassium ion coming in second. The magnesium ion is the most stable, with the calcium and strontium ions having the next most stable energetic values. The investigation of the M-N bond lengths corroborates the findings of the energetic criteria, confirming the same picture and ion selectivity. These differences in ion selectivity are a result of the differing flexibility of the two cryptands under investigation [2=N.2=N.2=N] and [2N=.2N=.2N=]. The cryptand [2=N.2=N.2=N] optimizes its dihedral angle to host guest cations effectively, while [2N=.2N=.2N=] gains greater flexibility from its C-N … N-C dihedral angle. The greater flexibility of [2N=.2N=.2N=] allows it to form a more suitable cavity to nest the guests due to the different location of the imine double bond in the bridges of the cryptates.
CRIS-Team Scopus Importer:2025-01-31
Keywords: cryptand; DFT; host-guest chemistry; Selective ion complexation